Catheter-related infections caused by Pseudomonas aeruginosa: virulence factors involved and their relationships - Olejnickova, Katerina; Hola, Veronika; Ruzicka, Filip (Pathogens and disease, 2014)
The nosocomial pathogen Pseudomonas aeruginosa is equipped with a large arsenal of cell-associated and secreted virulence factors which enhance its invasive potential. The complex relationships among virulence determinants have hitherto not been fully elucidated. In the present study, 175 catheter-related isolates were observed for the presence of selected virulence factors, namely extracellular enzymes and siderophore production, biofilm formation, resistance to antibiotics, and motility. A high percentage of the strains produced most of the tested virulence factors. A positive correlation was identified between the production of several exoproducts, and also between the formation of both types of biofilm. An opposite trend was observed between the two types of biofilm and the production of siderophores. Whereas the relationship between the submerged biofilm production (i.e. the biofilm formed on the solid surface below the water level) and the siderophore secretion was negative, the production of air-liquid interface (A-L) biofilm (i.e. the biofilm floating on the surface of the cultivation medium) and the siderophore secretion were positively correlated. All correlations were statistically significant at the level P = 0.05 with the correlation coefficient γ ≥ 0.50. Our results suggest that: (1) the co-production of the lytic enzymes and siderophores can play an important role in the pathogenesis of the catheter-related infections and should be taken into account when the virulence potential is assessed; (2) biofilm-positive strains are capable of forming both submerged and non-attached A-L biofilms; and (3) the different micro-environment in the submerged biofilm and A-L biofilm layers have opposite consequences for the production of other virulence factors.
Keywords: Virulence; dospělí; siderofory; Pseudomonas Infections; urinary tract; Enzymes; Virulence Factors; Female; Infant; katétrové infekce; dítě; předškolní dítě; novorozenec; Adult; ženské pohlaví; mladý dospělý; blood stream; Catheter-Related Infections; Adolescent; lidé; Infant, Newborn; Locomotion; virulence factors; Aged, 80 and over; bakteriální léková rezistence; virulence; Middle Aged; pseudomonádové infekce; lokomoce; Male; kojenec; Aged; Pseudomonas aeruginosa; Child, Preschool; Young Adult; biofilm; Siderophores; lidé středního věku; Child; senioři nad 80 let; biofilmy; senioři; mužské pohlaví; Drug Resistance, Bacterial; Biofilms; enzymy; mladiství; faktory virulence; antibiotic resistance; Humans